INSMART – Insights on integrated modelling of EU cities energy system transition. (April 2018) - G. Simoes, S.; Dias, L.; Gouveia, J.P.; Seixas, J.; De Miglio, R.; Chiodi, A.; Gargiulo, M.; Long, G.; Giannakidis, G.
Abstract: Urban areas have a pivotal role to play in climate change mitigation, as they are responsible for a high share of energy consumption and provide many opportunities for more efficient supply & use of energy. This makes the case for energy system modelling at city level, as done within the INSMART EU project, which identified the optimum mix of measures for a sustainable energy future for four European cities in a holistic manner. The approach combined quantitative modelling with Multi-Criteria Decision Analysis. Sector specific data and models (buildings and transport) were articulated into one integrated energy system model based on the TIMES model generator. It was found that urban level energy modelling brings with it a new set of challenges, since for a well-known territory, transparency and effective communication with local decision-makers are even more important than at national or transnational level. Special efforts should be paid to making model results geographically explicit, and urban modelling results should expect scrutiny by local agents. It was found that there is a gap between the scope for action of local energy planners and the most energy intensive urban sectors, which highlighted new priorities instead of those traditionally taken under municipal management. Highlights: We share insights on modelling EU cities decarbonisation pathways. We present the INSMART approach implemented in four European cities and countries. Urban energy systems modelling is useful but brings with it a new set of challenges. Balancing geographic explicitness, data availability and user ownership of results is fundamental. Urban energy systems modelling should be complemented with other tools for decision making.